THE EFFECT OF ADDITION SWIMMING CRAB SHELLS FLOUR (Portunus pelagicus) FOR PHYSICAL AND CHEMICAL QUALITY OF EDIBLE SPOON - Mohammad Rosikhul Ilmi Hussein Annafiz; Eko Nurcahya Dewi; Lukita Purnamayati (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2020)
Edible spoon product is a spoon-shaped cutlery that is fit to be eaten, this product was developed with the addition of alginate, however, it required high-cost raw material. Swimming crab shells were potential waste from underused swimming crabs which contained calcium carbonate (CaCO3) to strengthen the tissues, sources of calcium minerals, and formed edible spoon mixture. Swimming crab shells flour was the addition to the physicochemical quality of edible spoon and the best concentration for the product. This research utilized a completely randomized design (CRD) with different concentrations of swimming crab shell flour (0%, 8%, 10%, and 12%). The data were carried out with ANOVA and Tukey's HSD. The results showed that the addition of different swimming crab shell flour concentrations has a significant effect (P<5%) on the hardness parameters, melting time, hedonic properties, protein content, moisture content, carbohydrate content, and ash content except on fat content. The best concentration was 12% swimming crab shells flour with a hardness value of 10.32 ± 0.60 kgf, melting time of 15.02 ± 0.44 minutes, moisture content of 2.65 ± 0.24%, protein content of 8.31 ± 0.23%, carbohydrate content of 83.64 ± 0.29% , fat content of 1.42 ± 0.40% and ash content of 3.66 ± 0.06%. Edible spoon preferably has a hedonic value of 7.97 <µ <8.37 for appearance, odor, taste, and texture parameters.